2018
DOI: 10.1371/journal.pone.0195267
|View full text |Cite
|
Sign up to set email alerts
|

Association between particulate air pollution exposure during pregnancy and postpartum maternal psychological functioning

Abstract: Postpartum psychological functioning impacts both women’s health and outcomes in children. Lower income, ethnic minority women may be at particular risk for adverse postpartum mental health outcomes. Studies link ambient air pollution exposure with psychological dysfunction in adults although this association has not been examined among postpartum women.MethodsWe studied associations between prenatal exposure to particulate matter with diameter ≤ 2.5 μm (PM2.5) and postpartum psychological functioning in a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 42 publications
3
37
1
Order By: Relevance
“…Taken together, these discrepancies between different studies could be due to differences in PM2.5 exposure time and dosage. Moreover, evidences have shown exposure to PM2.5 in adulthood is an important risk factor for depression and anxiety symptoms in old adults and pregnant women (Pun, Manjourides, & Suh, ; Sheffield et al, ). However, the relationship between early postnatal exposure to PM2.5 and anxiety or depression phenotype in children and adults remains unknown at present; our findings provide experimental basis for relative epidemiological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these discrepancies between different studies could be due to differences in PM2.5 exposure time and dosage. Moreover, evidences have shown exposure to PM2.5 in adulthood is an important risk factor for depression and anxiety symptoms in old adults and pregnant women (Pun, Manjourides, & Suh, ; Sheffield et al, ). However, the relationship between early postnatal exposure to PM2.5 and anxiety or depression phenotype in children and adults remains unknown at present; our findings provide experimental basis for relative epidemiological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In stratified analyses, effects were most evident among African-American women. For this group of women, increased exposure to PM 2.5 was significantly associated with higher total postpartum EPDS scores as well as higher scores on the depressive and anhedonia symptom subscales, with minor variability in the identified window of vulnerability in pregnancy across these outcome measures (Sheffield et al, 2018).…”
Section: Analysis Of Resultsmentioning
confidence: 81%
“…The participants included an ethnically diverse, lower income urban cohort of pregnant women. The results demonstrated an association between prenatal ambient PM 2.5 exposure levels and postpartum total EPDS and the investigators observed a statistically significant sensitive window of PM 2.5 exposure for elevated anhedonia subscale scores during mid-pregnancy, especially gestational weeks 13 to 20 (Sheffield et al, 2018). In stratified analyses, effects were most evident among African-American women.…”
Section: Analysis Of Resultsmentioning
confidence: 81%
See 2 more Smart Citations